HUBUNGAN STRUKTURAL TINGKAT PENDIDIKAN, PENGALAMAN KERJA DAN USIA GURU DENGAN MOTIVASI KERJA DAN KEEFEKTIFAN KERJA TIM GURU SEKOLAH DASAR - Wiyono, Bambang Budi (Pendidikan Dasar, 2009)
Abstract, The research  is aimed to investigate the relationship between educational level, working experience, and age with work motivation and team work effectiveness of elementary school teachers, directly or indirectly. The population included teachers at elementary schools in Malang County. The sample, consisted of 438 teachers, was selected using proportional cluster random sampling. The research design was explanatory study in the form of causal modeling. The data, collected using questionnaire and documentation, were analysed by employing descriptive and structural equation modeling technique. The research found that there were structural  relationship between teachers educational level, working experience, and age with  their work motivation and team work effectiveness to do their professional tasks. .